Faktor-Faktor yang Berhubungan dengan Selisih Tarif Kasus Demam Berdarah Dengue - Prasaja, Bhisma Jaya; Utomo, Yoga; Firmansyah, Yura Witsqa (Lontara Journal of Health Science and Technology, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the Dengue virus and transmitted through the bite of the Aedes aegypti mosquito. The Bandung City Health Office said that this year as of April 26, 2024, the cumulative number of DHF cases in Bandung City exceeded 3,025 cases. This study aims to identify the factors associated between INA-CBGs tariffs and the actual treatment costs of Dengue Fever (DHF) patients at Hospital X Bandung. A correlation research method with a retrospective approach was used to analyze secondary data of JKN claims in 2023. The population in this study were patients who underwent inpatient treatment in 2023 at Hospital X Bandung with a diagnosis of Dengue Fever (DHF) with diagnosis code A91, totaling 906 medical record files. Samples were selected based on the criteria of medical record files with a primary diagnosis of Dengue Fever (DHF) and medical record files with JKN tariff setting. The results showed that length of stay (p < 0.001), medical procedures (p 0.018), and severity (p < 0.036) of illness significantly contributed to the tariff gap. This tariff gap has implications for the hospital's financial loss and potential reduction in service quality. Based on these findings, it is recommended to review the INA-CBGs tariff structure, develop clinical pathways, stricter management of treatment classes, and improve cooperation between hospitals and BPJS Kesehatan.